Antitumor effects of chemically modified miR-143 lipoplexes in a mouse model of pelvic colorectal cancer via myristoylated alanine-rich C kinase substrate downregulation - Jun Arima; Kohei Taniguchi; Nobuhiko Sugito; Kazuki Heishima; Yoshihisa Tokumaru; Yosuke Inomata; Kazumasa Komura; Tomohito Tanaka; Masa-Aki Shibata; Sang-Woong Lee; Yukihiro Akao (Elsevier, 2023)
Replenishing tumor-suppressor miRNAs (TS-miRNAs) is a potential next-generation nucleic acid-based therapeutic approach. Establishing an effective miRNA delivery system is essential to successful TS-miRNA therapy. To overcome vulnerability to RNA nucleases, we previously developed a chemically modified miRNA143-3p (CM-miR-143). In clinical practice, colorectal cancer (CRC) pelvic recurrence is an occasional challenge following curative resection, requiring a novel therapy because reoperative surgery poses a significant burden to the patient. Hence, we considered the use of CM-miR-143 as an alternative treatment. In this study, we used a mouse model bearing pelvic CRC adjacent to the rectum and investigated the anticancer effects of CM-miR-143 lipoplexes formulated from miRNA and a cationic liposome. Compared with commercial synthetic miR-143, CM-miR-143 lipoplexes accumulated heavily in regions of the pelvic CRC tumor where the blood flow was high. As a result, systemic administration of CM-miR-143 lipoplexes improved animal survival by significantly suppressing pelvic CRC tumors and relieving a lethal bowel obstruction caused by rectal compression. Detailed protein analysis revealed that the myristoylated alanine-rich C kinase is a novel target for CM-miR-143 lipoplexes. Our results suggest that CM-miR-143 is a potential next-generation drug candidate in the treatment of CRC pelvic recurrence.